Strategi Pemasaran Mobil Hybrid dalam Menghadapi Persaingan dengan Mobil Listrik China di Pasar Otomotif Indonesia - Afifahrahman, Fida; Khafidhatur, Kurnia (JPNM Jurnal Pustaka Nusantara Multidisiplin, 2025)
Indonesia's automotive industry is facing major changes as demand for environmentally friendly vehicles increases. The trend of car electrification, especially from Chinese manufacturers such as electric cars, has triggered increasingly fierce competition in the domestic market. In response to these changes, the launch of Hybrid Cars as compact SUVs that combine fuel efficiency and environmentally friendly technology. This research aims to analyze the marketing strategy of hybrid cars in the face of major competitors, especially Electric Cars, which offer cutting-edge technology at more competitive prices. This research uses a qualitative method with a case study approach, where data is collected through interviews with PT X parties, direct observation, and secondary data obtained from literature studies and related sources. The analysis was carried out using the STP approach, 7P marketing mix, SWOT, and NVivo software support. The results showed that hybrid has strengths in brand image, distribution network, and proven hybrid technology, but is faced with price challenges and consumer perceptions of Chinese electric cars. On the other hand, increasing public awareness of environmental issues and government support for electrified vehicles are strategic opportunities for Toyota to continue to improve the competitiveness of its hybrid products in the Indonesian market.